Theoretical perspective on the contextualization of teaching - Galbán Mendoza , Yumilka; Marín Granados, Laura Yazmín (Revista Minerva, 2022)
Undoubtedly, education occupies an important place in the life of every human being and not only for the mere fact of acquiring knowledge, but also because education allows the individual to manage to function in the world and integrate fully into his life, at the same time that develops their potentialities and capacities both human, intellectual and spiritual. The purpose of this article is to carry out an analysis from the theoretical perspectives that support the contexts in teaching, since the contexts that are taken into account for the development of teaching are diverse. For educational institutions within their actions is to systematically improve teaching contexts by focusing on the needs and characteristics of students so that they develop a reflective approach to learning. But under this premise it is necessary to recognize that there has not always been a reflection on teaching, its context or its contextualization, since it does not present a uniform content in didactic literature. Its conception comes to be based on the theoretical model of each actor, on the scientific current that positions it or on other theories that to a certain extent give meaning and organization to teaching.
Keywords: Context; Contextualization; Pedagogy; Didactics; Theoretical Conceptions